Cancer Profile in West Jakarta : A 5-year descriptive study - Gondhowiardjo, Soehartati Argadikoesoema; Handoyo, Denny; Auzan, Mahesa; Priharto, R Koesmedi; Yekti, Widyastuti Endro (Radioterapi & Onkologi Indonesia, 2018)
Background. Cancer burdens the government in terms of health care funding. Unlike  Indonesia, cancer information and data in other several countries are handled by a program called The National Program of Cancer Registries (NPCR), managed by Centers for Disease Control and Prevention (CDC). This study was aimed to describe cancer profile in West Jakarta Region from 2008 to 2012 due to insufficient data provided by the government.Methods. This was a cross-sectional, descriptive study involving all cancer patients residing in West Jakarta based on the medical record of Cipto Mangunkusumo Hospital, acting as DKI Jakarta Cancer Registry Control Center.Results This study found 4,057 cancer cases in the area. Five most commonly diagnosed cancer cases based on the sites of disease are breast cancer (22,5%), cervical cancer (10,3%), lung and bronchus cancer (7,5%), nasopharyngeal cancer (5,3%), and hemopoietic and reticuloendothelial malignancies (5,3%). Most cases were diagnosed in advance stage (III and IV) and predominantly in women aged 45 ? 54 years old. Intraductal carcinoma was the most common morphology type for breast cancer cases.